2020
DOI: 10.1039/d0cp03359f
|View full text |Cite
|
Sign up to set email alerts
|

Steric clash in real space: biphenyl revisited

Abstract: A textbook case of twisted structure due to hydrogen-hydrogen steric clash, the biphenyl molecule, has been studied in real space from a new perspective. Long-term discrepancies regarding the origin of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…The graphical representation of the reduced density gradient, sr=ρ()r/ρr4/3 , for the BP moiety in the crystal is shown in Figure 4(c); it does not provide any indication of steric strain involving the H⋅⋅⋅H contact but the non‐covalent nature of this interaction. A similar result has been recently reported for the planar isolated BP molecule [28] …”
Section: Resultssupporting
confidence: 91%
“…The graphical representation of the reduced density gradient, sr=ρ()r/ρr4/3 , for the BP moiety in the crystal is shown in Figure 4(c); it does not provide any indication of steric strain involving the H⋅⋅⋅H contact but the non‐covalent nature of this interaction. A similar result has been recently reported for the planar isolated BP molecule [28] …”
Section: Resultssupporting
confidence: 91%
“…A particularly controversial example is that of close H,H contacts in the planar conformer of biphenyl (Bph), which has been the subject of a raging debate for the last few decades. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The H,H contacts serve as a good case study of the difficulty in reconciling atomistic chemistry with holistic quantum approaches. In a recent study [23] on a purely MO-based description of the H,H contact in Bph, we have shown that (a) MO isosurfaces provide very little information on the contact or any other bond in the molecule, (b) each MO contributes in a vastly different nature to every diatomic interaction, and (c) only through the combination of all MOs in a molecule can an interaction be characterized in any meaningful manner.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that the region where the protobranches seems to appear in the alkanes studied here is above s(r)=0.60. Finally, we stablish that the classical steric clash situation in the studied compound comes from the interplay of attractive and repulsive NCI, as outlined in the reference [7] …”
Section: Discussionmentioning
confidence: 88%
“…As mentioned before, the main outcome in the analysis of the steric factors is the lack of rigorous definition. To date, different approaches and energy partition schemes have been proposed to quantify it, but there is no consensus about which is the best method [7,20–26] . Therefore, it is important to examine steric phenomena using methodologies which do not depend on the energy partition approximation.…”
Section: Introductionmentioning
confidence: 99%